2022
DOI: 10.3389/fvets.2022.917389
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Cattle With Recombinant Structural Ectodomains I and II of Babesia bovis Apical Membrane Antigen 1 [BbAMA-1(I/II)] Induces Strong Th1 Immune Response

Abstract: Both strong innate and adaptive immune responses are an important component of protection against intraerythrocytic protozoan parasites. Resistance to bovine babesiosis is associated with interferon (IFN)-γ mediated responses. CD4+ T cells and macrophages have been identified as major effector cells mediating the clearance of pathogens. Previously, the apical membrane antigen 1 (AMA-1) was found to significantly induce the immune response inhibiting B. bovis merozoite growth and invasion. However, a detailed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…It has been found that the Ab production induced by the B. bovis recombinant protein encoded by the conserved central region ( Bb AMA-1 ectodomain I (DI)and II(DII)) significantly inhibited Mrz growth as well as the efficiency of in vitro Mrz invasion of the bovine erythrocytes by 70% after 6 h, suggesting that this region is a good candidate for inclusion in an anti- B. bovis vaccine [ 51 ]. Such findings are consistent with a recent study which showed that cattle vaccinated with Bb AMA-1-DI/DII developed the humoral and the cellular responses which could be associated with protection [ 52 ].…”
Section: Anti-babesia Vaccinessupporting
confidence: 93%
“…It has been found that the Ab production induced by the B. bovis recombinant protein encoded by the conserved central region ( Bb AMA-1 ectodomain I (DI)and II(DII)) significantly inhibited Mrz growth as well as the efficiency of in vitro Mrz invasion of the bovine erythrocytes by 70% after 6 h, suggesting that this region is a good candidate for inclusion in an anti- B. bovis vaccine [ 51 ]. Such findings are consistent with a recent study which showed that cattle vaccinated with Bb AMA-1-DI/DII developed the humoral and the cellular responses which could be associated with protection [ 52 ].…”
Section: Anti-babesia Vaccinessupporting
confidence: 93%
“…These epitopes trigger the production of neutralizing antibodies and promote a durable Th1 immune response [ 21 ] Subunit Structural ectodomains I and II of B. bovis apical membrane antigen 1 [BbAMA-1(I/II)] Cattle that have been immunized with BbAMA-1(I/II) exhibit substantially elevated levels of total immunoglobulin (Ig)G antibodies, along with a heightened ratio of IgG2 to IgG1. Furthermore, this immunization has been found to induce a robust Th1 cell response in the vaccinated cattle [ 19 ] Live attenuated Stable transfected strain of B. bovis expressing an enhanced green fluorescent protein (eGFP) and a chimeric version of Bm86 ( B. bovis /Bm86/eGFP) Post-mortem analysis did not reveal any indication of parasites sequestering in the cerebral capillaries, which confirms that the strain has been attenuated. Additionally, this is the first documented case of B. bovis that has been genetically modified to express the tick antigen Bm86 on the surface of merozoites, triggering an antibody response against native Bm86 [ 26 ] Subunit Synthetic ß-(1 → 6)-linked glucosamine oligosaccharides conjugated to tetanus toxoid (5GlcNH 2 -TT) Experienced acute babesiosis, characterized by the adherence of infected erythrocytes to capillary vessels in the brain.…”
Section: Resultsmentioning
confidence: 98%
“…It is also important to assess the balance of pro- and regulatory cytokines (TNF-α, CXCL10, IFN-γ, IL-10, and IL-4) in the peripheral blood as a potential indicator of protection against acute Babesia infection Subunit [ 21 ] Despite using peptides of B. bovis antigens in vaccines that generate neutralizing immunity and involve CD4 + T cells, the resulting Th1 immune response was not effective in protecting vaccinated cattle against a virulent strain of B. bovis . This failure may be due to using a single antigen in the vaccine, which may not generate a strong enough immune response to block multiple stages of the invasion process • In this research, the scientists discovered peptides of MSA2c and AMA-1 that could generate neutralizing antibodies and IFN-γ, which is a Th1 cytokine associated with protection • However, it remains to be determined whether a combination of these peptides in a multi-antigen vaccine could enhance the effectiveness of the immune response, in terms of both humoral and cellular responses, or during exposure to a virulent strain Subunit [ 19 ] Different B. bovis strains that significantly hinder the effectiveness of live vaccines and pose a challenge in creating subunit vaccines • Considering that BbAMA-1's structural domains I and II can elicit both humoral and cellular immune responses, especially Th1 responses, BbAMA-1 is a promising vaccine candidate for bovine babesiosis • This is significant because strain variations pose challenges to live vaccines and subunit vaccine development. BbAMA-1, being highly conserved, has the potential to overcome strain-related issues by providing protective immunity against various B. bovis strains in real-world conditions Subunit [ 7 ] It is worth noting that B. bovis may not have all the necessary enzymes for complete N -linked glycosylation, unlike the Plasmodium parasite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation